(untitled) (Texas Journal of Engineering and Technology, 2026)
The article presents the results of studies on the technological parameters of an electrotechnological device used for pre-sowing ultraviolet treatment of maize seeds, as well as the optimal processing parameters for electrical stimulation and their relationship with crop yield indicators.